Determination of an acceptor level in bulk GaN grown by high nitrogen pressure solution method. Issue 5 (29th January 2015) - Dashdorj, J.; Zvanut, M. E.; Bockowski, M.
<x xml:space="preserve">Abstract</x> A point defect in acceptor‐doped bulk free standing GaN grown by the high nitrogen pressure solution method (HNPS) was investigated using electron paramagnetic resonance (EPR) spectroscopy. A nearly isotropic spectrum with g‐value of 1.984 is observed after illumination with 2.8 eV light and is stable after removal of the light. Comparison with earlier work on p‐type GaN films and SIMS data on the HNPS substrates suggests that the defect is related to an acceptor, heavily compensated during growth by oxygen. Time‐dependent photo‐EPR data are well modeled as a single defect‐to‐band transition where the defect level is 0.67 eV above the valence band edge. Although Mg‐ and Be‐doped samples were studied, only those samples containing Be produced the EPR signal. This observation, coupled with the similarity of the defect level measured to that predicted from the theory of others, suggests that the defect is related to a Be impurity.